Disasters and social crisis in contemporary Japan political, religious, and sociocultural responses - Mullins, Mark; Nakano, Koichi 1970- (Basingstoke, Hampshire Palgrave Macmillan, 2016)
"Japan is still coming to terms with the 'triple disaster' of 2011 -- earthquake, tsunami, and nuclear meltdown. Only two decades ago, the country was similarly shaken by the 'double disaster' of earthquake and sarin gas attack in 1995. What can we learn about Japan through the diverse responses to these two critical moments in postwar history when a 'normal' sense of stability and existing social order was severely undermined? This edited collection brings together a multidisciplinary team of scholars to engage this question and explore the wide-ranging and diverse responses by national and local governments, political leaders, citizen activists, concerned mothers, religious organizations, literary figures, and public intellectuals"--Provided by publisher.
Part I. Political responses -- Part II. Religious responses -- Part III. Social responses -- Part IV. Cultural responses.
Includes bibliographical references and index.
Keywords: Disasters -- Social aspects -- Japan; Human ecology -- Japan; Emergency management -- Japan; Disasters -- Social aspects; Emergency management; Human ecology; Japan